Conventional Anti-glioblastoma Chemotherapy Affects Proteoglycan Composition of Brain Extracellular Matrix in Rat Experimental Model in vivo - Tsidulko, Alexandra Y.; Bezier, Cynthia; de La Bourdonnaye, Gabin; Suhovskih, Anastasia V.; Pankova, Tatiana M.; Kazanskaya, Galina M.; Aidagulova, Svetlana V.; Grigorieva, Elvira V. (Frontiers in Pharmacology, 2018)
Temozolomide is a conventional chemotherapy drug for adjuvant treatment of glioblastoma multiforme (GBM), often accompanied by dexametasone to prevent brain edema and alleviate clinical side-effects. Here, we aimed to investigate an ability of the drugs to affect normal brain tissue in terms of proteoglycan (PG) composition/content in the experimental rat model in vivo. Age- and brain zone-specific transcriptional patterns of PGs were demonstrated for 8, 60 and 120 days old rats, and syndecan-1, glypican-1, decorin, biglycan and lumican were identified as the most expressed PGs. Dexamethasone (DXM) treatment affected both PG core proteins expression (mainly syndecan-1, glypican-1, decorin, biglycan, lumican, versican, brevican, NG2) and heparan sulfate (HS) and chondroitin sulfate (CS) content in organotypic brain slice culture ex vivo and experimental animals in vivo in a dose-dependent manner. Temozolomide (TMZ) treatment did not result in significant changes in PG core proteins expression both in normal rat brain hippocampus and cortex in vivo (although generics did), but demonstrated significant effects onto polysaccharide HS/CS content of the brain tissue. The effects were age- and brain zone-specific and similar with the age-related PGs expression changes in rat brain. Combination of TMZ with DXM resulted in the most profound deterioration in PGs composition and content in the brain tissue both at core protein and glycosaminoglycan levels. Taken together, the obtained results demonstrate that conventional anti-glioblastoma therapy affect proteoglycan structure and composition in normal brain tissue, being a negative factor involved in brain ECM deterioration and formation of the favorable tumorigenic niche for the expansion of the residual glioma cells. During the TMZ chemotherapy, dose and regimen of DXM treatment matter, and repetitive low DXM doses seem to be more sparing treatment compared with high DXM dose(s), which should be avoided where possible, especially in combination with temozolomide.